The Implementation of Local Wisdom-Based Character Education in Elementary School - Badeni; Sri Saparahayuningsih (Journal of Educational Issues, 2024)
The majority of people believe that character education based on local wisdom in primary school may help children acquire moral values, great behavior, and character for students who embody society’s culture and character. However, the question is what sort of learning model may be used in teaching character in primary schools. The fundamental purpose of this study is to investigate the implementation of a local wisdom-based character education model for moral character development based on local wisdom values. The study used qualitative methodologies in the form of a phenomenological plan (design). Data was acquired through observations, interviews, focus group discussions, and document examinations. Data analysis techniques include data reduction, data visualization, and conclusion drafting. Based on the outcomes of this study, it can be concluded that enforcing the local wisdom-based character education model may be used as an alternative option and that learning models imposing character values may have the benefits and potential of local wisdom values. The model’s implementation is incredibly effective in developing students’ personalities. The majority of students changed their behavior, attitudes, and character by being more driven to study, more disciplined in their behavior, more responsible for their acts, making commitments, being honest, and striving for perfection. Why do they become like that? As part of their learning process, they always ponder why the norms, values, and regulations should be followed.